(untitled) (Texas Journal of Medical Science, 2026)
The study comprehensively assessed the relationship between the severity of patients’ general condition and liver function in patients with concomitant facial bone injuries. Biochemical and oxidative parameters were analyzed in 122 patients using clinical data, international severity assessment scales (ISS, GCS, PTS, PELOD), and laboratory test results. It was found that the severity of systemic inflammation and cytolysis, decreased protein-synthetic function of the liver, and impaired coagulation status correlated with the severity of traumatic injury. Patients receiving hepatoprotective therapy demonstrated more favorable dynamics of these parameters and more rapid clinical improvement. The obtained data confirm the significance of liver markers as prognostic criteria and emphasize the role of liver function correction in the comprehensive treatment of concomitant facial bone injuries